Exploratory insights into audit fee increases: A field study into board member perceptions of auditor pricing practices - Francis Goddard; Martin Schmidt (International Journal of Auditing, 2021)
Audit research documents audit fee discounts associated with an auditor change, and that audit fees revert to average levels within a few years. This paper provides exploratory insights into the perceptions of board members vis-à-vis pricing practices used by auditors to achieve audit fee increases. In semi-structured interviews with 12 respondents (10 board members and two audit managers), we elicit perceptions on initial audit fee discounts, auditor pricing practices and client reactions to these pricing practices. The key findings indicate that auditors combine two pricing practices to achieve audit fee increases. First, they negotiate higher fees prior to the annual audit cycle, citing changes in client structure/size and the institutional environment. Second, they charge higher than negotiated fees after completing the audit (`extra-billing'), citing justifications such as chargeable hour overruns and findings warranting additional work. Potentially, such auditor pricing practices have negative implications for audit quality and damage the auditor–client relationship.
Keywords: 650; audit fee discounts; audit fee increases; audit quality; auditor pricing practices; extra-billing; lowballing